Campus Accessibility for Persons with Disabilities at State Islamic University of Alauddin Makassar: A Maqāṣid al-Sharī‘ah and Universal Design Policy Perspective - Fajar Fajar; Firdaus Firdaus (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
This study aims to examine and analyze the level of accessibility of buildings at State Islamic Higher Education Institutions (PTKIN), particularly UIN Alauddin Makassar, in accommodating the needs of persons with disabilities from the perspective of maqāṣid al-sharīʿah and Universal Design policies. Since there has been no comprehensive research that integrates the maqāṣid al-sharīʿah perspective with universal design policies in the context of PTKIN, most previous studies have been conducted at general public universities, leaving PTKIN relatively unexplored. This study aims to fill that gap by examining and analyzing the level of building accessibility at UIN Alauddin Makassar. This study uses a descriptive qualitative approach with data collection techniques in the form of direct observation of physical infrastructure, in-depth interviews with students with disabilities, and a review of relevant policies and regulations. The results show that most campus facilities do not meet the physical accessibility standards as stipulated in the Minister of Public Works and Public Housing Regulation No. 14 of 2017, and have not systematically integrated the principles of Universal Design in the planning and development of facilities. This condition also reflects a discrepancy with the principles of maqāṣid al-sharīʿah, particularly those related to the protection of reason (ḥifẓ al-ʿaql), the protection of life (ḥifẓ al-nafs), and respect for human dignity (karāmah al-insān). Therefore, continuous structural improvements, data-driven policy development, and strengthened institutional commitment are needed to create an inclusive, fair, and civilized campus environment for the entire academic community, including persons with disabilities.